2011
DOI: 10.1007/s00264-011-1362-z
|View full text |Cite
|
Sign up to set email alerts
|

Bone marrow-derived mesenchymal stem cells versus bone marrow nucleated cells in the treatment of chondral defects

Abstract: These data indicate that BNCs contribute to the repair of cartilage with collagen type II hydrogel as scaffolds, which have comparable results with bone marrow-derived MSCs. Moreover, the transplantation of autologous BNCs as seed cells may be a more economical and convenient technique for cartilage repair in clinical applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
29
0
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 25 publications
1
29
0
2
Order By: Relevance
“…Various cell types and materials were tested in the studies. Zhang et al compared bone marrow-derived MSC and uncultured bone marrowderived nucleated cells (bone marrow concentrate) in a pig model and reported that the results of both groups were comparable [40]. The results of this study seem to support the feasibility of a one-step procedure in a clinical setting.…”
Section: Large Animal Studiessupporting
confidence: 68%
See 2 more Smart Citations
“…Various cell types and materials were tested in the studies. Zhang et al compared bone marrow-derived MSC and uncultured bone marrowderived nucleated cells (bone marrow concentrate) in a pig model and reported that the results of both groups were comparable [40]. The results of this study seem to support the feasibility of a one-step procedure in a clinical setting.…”
Section: Large Animal Studiessupporting
confidence: 68%
“…Among those, a (mini)pig model has been most frequently employed in previous studies [37][38][39][40][41][42][43][44]. Various cell types and materials were tested in the studies.…”
Section: Large Animal Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, in contrast to mature chondrocytes, MSCs can be expanded ex vivo to sufficiently high numbers, making them an abundant cell source for autologous cell therapies. Unfortunately, it is difficult to obtain a pure population of stem cells, as well as precisely control the direction of MSC differentiation [61]. Another disadvantage is the relatively low percentage of MSCs in bone marrow; moreover, in the elderly, the cell proliferation rate of isolated MSCs is often insufficient.…”
Section: Mesenchymal Stem Cellsmentioning
confidence: 99%
“…The composition of these nucleated cells is diverse that includes MSCs, Hematopoietic Stem Cells (HSCs), Monocyte Precursor cells, Macrophages, T cells, B cells, Dendritic Antigen Presenting Cells, Natural Killer Cells and Neutrophils. [77][78][79] Nevertheless, BMC serves as a source of growth factors, including platelet-derived growth factor (PDGF), transforming growth factor-beta (TGF-β), and bone morphogenetic protein (BMP)-2 and BMP-7, which are assigned to have anabolic and anti-inflammatory effects that facilitate regeneration of tissue. [80][81][82] The resultant BMC after centrifugation has been shown to provide elevated levels of HSCs, MSCs, platelets, chemokines and cytokines that are injected intra-articularly for treating cartilage defects.…”
mentioning
confidence: 99%